2018
DOI: 10.1038/s41598-018-23270-0
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide uptake by colloidal and particulate humic acids obtained from 14 soils collected worldwide

Abstract: Uptake of six particle-reactive and/or redox-sensitive radionuclides (210Pb, 234Th, 7Be, 59Fe, 237Np and 233Pa) by 14 humic acids (HAs) was investigated in artificial groundwater under mildly acidic conditions (pH~5.5). In HA-groundwater slurry, Pb, Be, Fe and Pa bound strongly to particulate HA (>0.45 µm), supporting their application as tracers of soil erosion. Th bound strongly to the colloidal HA (3 kDa-0.45 µm) and as such, would not be a good candidate as a tracer for monitoring soil erosion. HAs likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Subsequent to their deposition, chemical similarities between 7,10 Be and 210 Pb argue that their congruent behaviors and coherent sources will be maintained through transport in terrestrial systems. Each of the FRNs is characterized by empirical partition coefficients (K D ) on the order of 10 4 and is thus considered highly “particle reactive” (Lin et al., 2018)—they bind rapidly to ambient surfaces, materials, and particles, and are commonly assumed to trace bulk soils and sediments (Mabit et al., 2013; Robbins, 1978; Ryken et al., 2018; Taylor et al., 2013; Willenbring & von Blanckenburg, 2010). Thus, through shared processes of atmospheric production, aerosol scavenging, deposition, and transport, fluxes of 7 Be and 210 Pb are strongly and universally correlated at sites around the globe (e.g., Baskaran et al., 1993; Du et al., 2015; Todd et al., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to their deposition, chemical similarities between 7,10 Be and 210 Pb argue that their congruent behaviors and coherent sources will be maintained through transport in terrestrial systems. Each of the FRNs is characterized by empirical partition coefficients (K D ) on the order of 10 4 and is thus considered highly “particle reactive” (Lin et al., 2018)—they bind rapidly to ambient surfaces, materials, and particles, and are commonly assumed to trace bulk soils and sediments (Mabit et al., 2013; Robbins, 1978; Ryken et al., 2018; Taylor et al., 2013; Willenbring & von Blanckenburg, 2010). Thus, through shared processes of atmospheric production, aerosol scavenging, deposition, and transport, fluxes of 7 Be and 210 Pb are strongly and universally correlated at sites around the globe (e.g., Baskaran et al., 1993; Du et al., 2015; Todd et al., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its hydrophilic and hydrophobic functional groups and high flexibility, HA is amphiphilic and can potentially bind with toxic heavy metal ions such as actinides and organic matter such as polycyclic aromatic compounds (PAC). Earlier studies on its interaction with uranyl often used HA as an additive to investigate its influence on the adsorption of uranyl on adsorbents, and a small amount of work focused on the cooperative adsorption. In the work of Song et al, the mutual influence of uranyl and HA on their simultaneous removal from an aqueous system by the synthesized cyclodextrin-modified graphene oxide nanosheets (CD/GO) has been investigated, which indicated that the presence of HA enhanced uranyl sorption at low pH and reduced uranyl sorption at high pH, while the presence of uranyl enhanced HA sorption. The surface adsorbed HA acted as a “bridge” between uranyl and CD/GO and formed strong inner-sphere surface complexes with uranyl.…”
Section: Introductionmentioning
confidence: 99%
“…Specific minerals, ligands, or macromolecules that FRNs may favor in sorption are becoming a focus of experimental work. Contextualizing experimental results remains a challenge, however, due to the complexity and breadth of geochemical systems. FRN speciation is determined by interacting cofactors including production source, depositional process, aerosol chemistry, and particle age, and through these factors, FRN atmospheric deposition represents multiple aerosol populations .…”
Section: Introductionmentioning
confidence: 99%